THE EFFECT OF JOB SATISFACTION TOWARD HEALTH WORKER'S SERVICE QUALITY OF VILLAGE HEALTH COTTAGE IN SITUBONDO DISTRICT - Andayani, Kartika Sari; Sugiyanta; Iqbal, Muhammad (The Indonesian Journal of Public Health, 2024)
Introduction:  The quality of health worker services is an important parameter to increase the pace of health development. The decline in the quality of health worker services was caused by a decrease in the job satisfaction of health workers. Based on the report on standardization of the quality of Ponkesdes services at the Situbondo District Health Office (2020), the number of Ponkesdes that received the title of "fulfilling" in 2020 has decreased from the previous year by 8%. Aims: To determine the effect of job satisfaction on the quality of service for health workers. Methods: This type of research uses explanatory research. The sample of this study was 268 nurses and midwives at village health cottage in Situbondo Regency. Data collection techniques were compiled on the Google Form platform and distributed in the form of links through social media groups. Data analysis used path analysis through multiple linear regression. Results: The results of the path analysis study show that the work motivation and competence of health workers in Pondok Sehat Desa in Situbondo Regency substantially influence job satisfaction. Employee satisfaction at Pondok Sehat Desa greatly influences the quality of health services. Conclusion: The government can provide health worker development programs and remuneration restructuring that can stimulate the intrinsic and extrinsic motivational elements for health workers at Village Health Cottage in Situbondo Regency. It is vital to create a health service management roadmap.